PERCEIVED VALUE AND CUSTOMER SATISFACTION OF SMARTPHONE BRAND AMONG YOUTH: THE MODERATING EFFECT OF GENDER - Sondoh Jr., Stephen Laison; Ming Fook, Lim; Tanakinjal, Geoffrey Harvey; Ling Chai, Wong (Malaysian Journal of Business and Economics (MJBE), 2020)
Advances in technology have made mobile phones develop into smartphones. It is undeniable that the smartphone has brought many benefits to users and has become an indispensable part of our daily work. This situation reflects the consumer nowadays hard to ignore the value of the smartphone. Hence, smartphone developers need to understand the value of smartphones, especially for immature groups such as youth in Malaysia. This is because values that are perceived as positive will drive positive results or vice versa. Unfortunately, far too little attention being stressed on this issue. Therefore, the current study is aimed to examine the relationship between perceived value and customer satisfaction in the context of youth smartphone users. Besides, the study also inspects the moderating effect of gender on the relationship between perceived value and customer satisfaction. In terms of data collection, a complete set of data received from 306 respondents via snowball sampling and analyzed by Statistical Package for the Social Sciences. The multiple regressions analysis result revealed all the five dimensions of perceived value have a positive influence on customer satisfaction. However, the social value was confirmed has a negative and significant effect on customer satisfaction. The moderated regression analysis results indicated that male is satisfied when they perceived high monetary value of the smartphone meanwhile female is satisfied with the smartphone when they perceived high emotional value acquired from using the brand compared to male. Based on the findings, the study suggests that marketers and smartphone manufacturers need to take suitable marketing approaches for a different group of consumers (i.e. gender) to achieve customer satisfaction. It is also crucial to understand the values obtained by consumers from using the smartphone brand. Knowing this may assist managers to develop a strong brand in the marketplace.